PROYEK PROFIL PANCASILA SEBAGAI UPAYA MENUMBUHKAN JIWA ENTREPRENEURSHIP PADA PESERTA DIDIK - Maskurotun Nadhirah; Lufiah, Qonita; Hadiyanto (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The purpose of this research is to understand the profile of Pancasila students as an effort to foster the spirit of entrepreneurship in students. In this research, the author uses a qualitative approach with descriptive methods. The results of this study indicate that the independent curriculum is the most optimal curriculum in fostering the spirit of entrepreneurship in students through the development of the Pancasila student profile. Where in the development of the Pancasila learner profile, project-based learning activities are carried out. So, it is hoped that in the future students will become a creative, independent society and be able to face economic problems in Indonesia in accordance with the values of Pancasila.